Comparison of CdS Thin Films Prepared by the Traditional and Shallow Chemical Bath Deposition Method. Issue 12 (30th September 2022) - Alvarado, Jose Alberto; Ramírez‐Velasco, S.; Reyes‐Gracia, A.; Vigil‐Galán, O.; Hernández‐Calderón, V.; Cuapio, Rene Perez; Roque, J.; Arce‐Plaza, A.
Abstract: Chemical bath deposition (CBD) is one of the most used methods for CdS thin films deposition, but nevertheless, the by‐product from the reaction constitutes a source of gross contamination. To reduce these residues, shallow‐CBD (S‐CBD) is proposed as an alternative method. Albeit this method only requires 25% of solution compared to traditional‐CBD (T‐CDB), making this method suitable to be used in device fabrication technology. In this work, a comparison between both techniques idone through the optical (UV–vis), structural (X‐ray diffraction), morphology (scanning electron microscopy), and electrical properties such as four‐point resistivity and temperature–current dependence from CdS layers analysis, deposited by S‐CBD and T‐CBD, is reported. Abstract : Shallow chemical bath deposition (CBD) offers a competitive advantage over traditional ones, offering yield material, reuse of it, and reproducible results making it scalable in device applications compared to traditional CBD.